Konsep diri pada remaja broken home (Universitas Negeri Padang, 2021)
The study aims to understand the effects of a broken home family on a teenager's concept of self and to understand the psychological condition of the teen affected by the broken home family. The method used in this article is that of literary study. In the study, researchers made a diligent search of the library that was needed in the study. Library or library studies are activities related to library methods of collecting data that can be found in books, journals, and articles by reading and writing and processing research materials (zed, 2003, h.3), in this article will discuss good youth concepts and how the spirit teacher's role in helping students cope.